(untitled) (BSAA arte, 2020)
This paper covers the controversy raised in 1990 in the British Museum about the authenticity of the three enamelled gold dog pendants, garnished with precious stones, from the Treasury of the Pillar in Saragossa that were publicly auctioned in 1870 and still remain spread. These pendants, were considered fakes manufactured c. 1860 by the historiography. Nevertheless, I can prove that the documentation of the Pillar shows that at least two of them were authentic Renaissance works (c. 1580-1600). At the very least, two European counterfeiters copied genuine works, which raises the revision of the history of goldsmithing from works that are clearly genuine.